Por uma leitura deleuziana das crônicas claricianas: poiésis e rostidade - Silva, Maria Eliane Souza da (2015)
The text establishes a debate between the work of Clarice Lispector and theories of philosophical thought of Gilles Deleuze and Félix Guattari , watching from the meeting of the authors, the agency of a “deed Glide” regarding the various discursive interrelationships of chronic clariciana. Thus, the concept of “face” of the French philosophers as “abstract machine” subsidize our discussion at the prospect of “deformable combinations of gears” of the genre. It is observed also in this context the setting of a literary cartography which sketches out an everyday poiesis in the movements of deterritorialisation and re-signification of multiple images established by the author.